ANALYSIS OF THE SOCIAL NORM OF RECREATIONAL CAPACITY AND TOURIST SATISFACTION ON THE SOUTH-WESTERN SHORE OF LAKE ALAKOL - Adilet G. VALEYEV; Akhmetkal R. MEDEU; Aiman A. ZHAKUPOVA; Kamshat B. YEGEMBERDIYEVA; Zhanerke M. SHARAPKHANOVA (Geo Journal of Tourism and Geosites)
The study is aimed at determining the social norm of the density of people on the beach and identifying the weaknesses of the organisation of beach-bathing tourism for the rational use of recreational resources and the development of sustainable tourism. Aerial photography of the coast and conducting a sociological survey of vacationers, statistical approaches and Importance-Performance Analysis were used. The total threshold density on the beaches is estimated at 14 627 vacationers (3 m2/person), acceptable density at 5 683 vacationers (8 m2/person). Safety issues in the water area, pollution of the coast and lack of awareness among tourists are recommended for priority solutions. The results will improve the quality and safety of tourists' recreation and generally lay the foundation for the rational use of recreational resources and development of sustainable tourism on Lake Alakol.